An unprecedented deoxygenation protocol of benzylic alcohols using bis(1-benzotriazolyl)methanethione1. Issue 40 (7th May 2015) - Kumar, Dhananjay; Singh, Anoop S.; Tiwari, Vinod K.
<x xml:space="preserve">Abstract</x> A new method of silane or Bu3SnH promoted radical deoxygenation of benzylic alcohols using bis(1-benzotriazolyl)methanethione has been developed.